Ética na liderança organizacional com base nas bem-aventuranças - Silva, Gleibson de Andrade Arruda (2013)
The object of the present research work is to analyze ethics in leadership more specifically identified in the biblical text of the Gospel according to Matthew 5:3-11 wrote. As well, the implications in the use of every virtue in the above organizational leadership aiming perennial organizational success and the achievement of personal and collective involved in this activity. Due to the increasing complexity in the organizational space and the constant need for change, every leader needs a number of skills that promote change and lead projects leading companies operating perpetuity, without, however, losing the ability to achieve happiness and personal and collective. The full development and enduring organizations, assumes that all leadership must develop skills that enable organizational development, given the need for change management that produce productivity gains and aggregating the performance of those involved in the direction and operation of the organization. You need to consider issues such as spirituality and transcendental sources that directly influence the relations of organizational leadership so the beatitude composes a program or even a culture that propagates values into disuse as humility, kindness and mercy. By assuming the need for every leader must understand his spirituality sharing and applying the virtues exhibited in the beatitudes is defined as a code of ethics, more specifically Christian ethics. Ethics extracted from bliss, is actually a different kind of ethics and unusual in the corporate world. It should reaffirm the values-based leadership, which are in full swing arguably influenced by cultural objective question, but also by subjective issues, including spirituality and transcendentalism, then the question of ethics is cultural, structural and cyclical. To be happy humans can take place can walk down a path more individualistic and self-centered, but to achieve the ideal of "more than happy" or blessed is necessary to break with several paradigms structural market and the academy of sciences administrative.